The Reform of British Industrial Relations : The Donovan Report and the Labour Government’s Policy Proposals - Banks, Robert (Relations industrielles / Industrial Relations, 1969)
Against a background of recurrent economic crisis in the 1960s pressures have developed to reform Britain's traditional industrial relations system. During the last two years the report of The Royal Commission on Trade Unions and Employers' Associations and a subsequent Labour Government White Paper included significant recommandations which are likely to change the character of the traditional system. Nevertheless both documents support an essentially voluntary approach to the reform of collective bargaining and reject the transformation of collective agreements into legally binding contracts. However, as a result both of growing public support for additional reforms and the improvement in the Conservative Opposition's political fortunes, plus doubts about the capacity of British unions and management to improve collective bargaining procedures voluntarily, the author suggests that further Government intervention in industrial relations is a strong possibility in the next few years.